Decentralization and Local Democracy in the World : First Global Report by United Cities and Local Governments 2008 - United Cities and Local Government (Washington, DC: United Cities and Local Government and the World Bank, 2012)
This overall picture of decentralization and local democracy in African countries shows significant progress at the strictly institutional level. No country now publicly opposes the implementation of decentralization policies. Local governments exist in all countries, and elections are held to elect local authorities. The extent of such progress must, however, be set against a number of persistent obstacles that continue to hinder a real progression of decentralization in Africa. Difficulties remain within states concerning the transfer of financial resources needed to match the devolved responsibilities. Local governments also face difficulties in increasing their own resources (aside from state-transfers and grants) at a faster pace. Ensuring the availability of qualified human resources at the local level and improving public access to local services are also fundamental issues of concern.